User Survey update - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
'Count me in!' a dozen readers call out each week, with belated letters and emails, keen to join the Spore User Survey which officially closed several months ago. Do not worry, your views have been noted, even if some latecomers have not been...